EXPERIMENTAL INVESTIGATION ON THE TRI-DIRECTIONAL QUASI-STATIC OF POT-SHAPED METAL RUBBER (MT) - WANG Wei; TANG Yu; WU YiWan; BAI HongBai; LU ChunHong (Jixie qiangdu)
In order to meet the demand of three-way vibration reduction of metal rubber, a pot-shaped metal rubber was designed and prepared via introducing spatial configuration. The method of controlling variables to study the effect of preparation process parameters such as relative density, forming angle, wire diameter and compression on the static mechanics of pot-shaped metal rubber was investigated, and the influence of three preparation process parameters on the pot-shaped metal rubber axial and radial static mechanics was revealed by orthogonal test method. The results show that the sequence that affects the axial static mechanical properties of the test piece is forming angle, relative density, and wire diameter; the sequence that affects the radial static mechanical properties of the test piece is relative density, wire diameter, and the forming angle.